Canting and communication: Women’s role in preserving traditional batik culture in Kampung Batik Giriloyo, Yogyakarta - Az-Zahra, Alifia Wanda; Wibowo, Arif Ardy; Tur, Ajar Pradika Ananta (NOTION: Journal of Linguistics, Literature, and Culture, 2025)
This study examines the dual role of women in Kampung Batik Giriloyo as housewives and cultural practitioners who preserve the tradition of hand-drawn batik. Using a qualitative case study approach combined with Standpoint Theory, this study argues that batik making for women is not merely an economic activity, but also a medium for cultural transmission and challenging patriarchal norms. The role of the Sido Mukti batik group emerges as an important mediator in communication and economic aspects, with the process of intergenerational knowledge transfer beginning in childhood, and the specific challenges of competition from printed batik being an important point in this study. Data obtained from interviews and observations show how women transform their domestic identities into cultural leadership in the public sphere, despite being hindered by systematic gender barriers. It is hoped that the results of this study can provide a comprehensive interpretation of women’s contributions to the preservation of hand-drawn batik culture. These findings are intended as a reference for efforts to empower women and preserve traditional culture in Indonesia.